1994
DOI: 10.21273/hortsci.29.12.1511
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain Reflectometry for Measuring Water Content of Organic Growing Media in Containers

Abstract: The time-domain reflectometry (TDR) method of measuring water content has been applied to mineral soils but not to organic growing media. We investigated the applicability of TDR for measuring the water content of organic media in containers. TDR calibration was conducted for sand, peat, composted pine bark, sand and peat mix, sand and bark mix, and a commercial growing medium (Metro Mix 300). Regression analysis of volumetric water content was conducted with the ratio of apparent: physical length of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
(45 reference statements)
0
17
0
1
Order By: Relevance
“…There were three replications of three plants for each watering regime, and the replications Vi'ere organized in a randomized complete block design. The volumetric water content of the growing medium was monitored by lime-domain reflectometry as described by Anisko et al, (1994), A randomly selected pot in each block x watering regime was used for monitoring water content of the growing medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were three replications of three plants for each watering regime, and the replications Vi'ere organized in a randomized complete block design. The volumetric water content of the growing medium was monitored by lime-domain reflectometry as described by Anisko et al, (1994), A randomly selected pot in each block x watering regime was used for monitoring water content of the growing medium.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies on woody plants have implied that Similarly, the symplastic water fi'action, the relative changes in cold hardiness and tissue water relations pa-water content at the turgor loss point, water potential at ratneters may be related (Tyree et al, 1978, Roberts et al, the turgor loss point, and osmotic potential decrease dtjr-1980, Ritchie and Shula 1984, Teskey et al, 1984, Doi et mg cold acclimation and later increase during deacclimaal, 1986Gross and Koch 1991Grossnickie 1992, Tis-tion (Roberts andKnoerr 1977, Tyree et al, 1978, Roberts sue water content has been observed to decrease m vari-et al, 1980, Ritchie and Shula 1984, Teskey et al, 1984, ous species during cold .acclimation (Roberts and Knoen-Doi et al, 1986, Auge and Stodola 1989, Grossnickie 1977Bray and Parsons 1981Grossnickie 1992, The 1992), In contrast, the maximum bulk modules of elasftcwater loss observed during cold acclimation may be only ity increases during cold acchmation and decreases durapparent water loss as the result of dry matter accumula-tng deacdimation in the spnng (Ritchie and Simla 1984, Auge and Stodola 1989, Grossnickie 1992, These changes parallel those obsei-ved in woody plants subjected to drought (Bongarten atid Teskey 1986, Abrams 1988, Parker and Pallardy 1988, Zwiazek 1991, Increased cold hardiness induced by water stress has been reported for many plants (Chen and Li 1977, Yelenosky 1979, Biddington and Dearman 1988, Anisko and Lindstrom 1995, Mechanisms proposed to explain the water-stress-induced increases in cold hardiness include either the removal of nonessentia! water which could participate in mechanically damaging crystallization during freezing (Li and Weiser 1971) or the depression of the freezing temperature which is associated with a decline in osmotic potential (Li and Weiser 1971…”
mentioning
confidence: 87%
“…No soil specific calibrations are required (Topp and Davis, 1985;Zazueta and Xin, 1994;Ferrara and Flore, 2003). This technique gives accurate results within an error limit of ±1% and allows continuous measurements to be obtained over the full soil moisture range (Anisko et al, 1994;Chandler et al, 2004), along with measurements of the electrical conductivity of the soil (Robinson et al, 2003;Thomsen et al, 2007). However, the probe length influences the accuracy of moisture measurement (Richardson et al, 1992).…”
Section: Time Domain Reflectometrymentioning
confidence: 99%
“…Composts are substance-specific porous materials and it is anticipated they will exhibit different physical and hydraulic properties. Until now, very little work (da Silva et al, 1998;Anisko et al, 1994) concerning the methodology of their moisture content determinations has been presented and therefore we believe that their inclusion in this present attempt is worthwhile. Samples 18, 19 and 20 consist of mixtures of volumetric percentages 25% peat, 50% perlite and 25% compost of the composts described above.…”
Section: Porous Materials Usedmentioning
confidence: 99%